PREDICTIVE TESTING AND EXISTENTIAL ABSURDITY: RESONANCES BETWEEN EXPERIENCES AROUND GENETIC DIAGNOSIS AND THE PHILOSOPHY OF ALBERT CAMUS - Porz, Rouven (Bioethics, 2011)
Predictive genetic testing may confront those affected with difficult life situations that they have not experienced before. These life situations may be interpreted as ‘absurd’. In this paper we present a case study of a predictive test situation, showing the perspective of a woman going through the process of deciding for or against taking the test, and struggling with feelings of alienation. To interpret her experiences, we refer to the concept of absurdity, developed by the French Philosopher Albert Camus. Camus' writings on absurdity appear to resonate with patients' stories when they talk about their body and experiences of illness. In this paper we draw on Camus' philosophical essay ‘The Myth of Sisyphus’ (1942), and compare the absurd experiences of Sisyphus with the interviewee's story. This comparison opens up a field of ethical reflection. We demonstrate that Camus' concept of absurdity offers a new and promising approach to understanding the fragility of patients' situations, especially in the field of predictive testing. We show that people affected might find new meaning through narratives that help them to reconstruct the absurd without totally overcoming it. In conclusion, we will draw out some normative consequences of our narrative approach.